Influence of Prospective and Situational Sets on the Correctness of Probabilistic Judgments - Charkviani, David; Dzidziguri, David (European Scientific Journal, ESJ, 2017)
Investigation of psychical mechanisms of probabilistic thinking revealed its limited rationality, reflecting specificity of subjective comprehension of one on other problem by people. The concepts satisfying the theory of probabilistic thinking are impersonal, and determined by psychic mechanisms are personal. In case of personal rationality cognitive activity of people serves to satisfaction of different needs people have. Besides, when making decision they reveal purposive playing an important role in assessment of alternatives out of multiple possible choices. Considering the main principles of the set theory, we assume that functioning of probabilistic judgments is determined by relevant set formed in the process of purposive activity of human. As to temporary parameter, two forms of the set can be defined: prospective (orientation on the result of future event) and situational (orientation of the result of current event). In the conducted experiment the influence of the above mentioned sets on probabilistic judgments and confidence in correctness of the choice taking into feedback factor (mark of the fulfilled task) was studied.